Temporal dynamics and demographic specificity of provider-initiated HIV testing in China: an eight-year retrospective analysis - Sun, Yuexin; Wu, Qiaofang; Tao, Yue; Yu, Haoyue; Zhou, Ying; Bao, Jun (Frontiers in Public Health, 2025)
BackgroundThis study evaluates the effectiveness of PITC implementation at Nanjing Drum Tower Hospital from 2017 to 2024 and examines variations in testing efficiency across different populations and time periods, aiming to provide critical evidence for adjusting PITC strategies to adapt to epidemiological changes.MethodsA cross-sectional analysis study was conducted on 907,395 patients who underwent HIV testing at Nanjing Drum Tower Hospital from 2017 to 2024. Patients were divided into routine testing group (RT group) (n = 879,503) and PITC group (n = 27,892). Chi-square tests and Cochran-Armitage trend tests were employed to compare HIV positivity rates and temporal trends between the two groups.ResultsThe overall HIV positivity rate in the PITC group (0.51%) was significantly higher than in the RT group (0.10%) (χ2 = 718.5, p < 0.001), although the effect size was modest (V = 0.028). Time trend analysis revealed a significant decline in the positivity rate within the PITC group, from 0.83% in 2017 to 0.30% in 2024 (Z = −2.96, p = 0.003). In contrast, the positivity rate in the RT group remained relatively stable (0.07–0.13%). The PITC group was predominantly male (67.5%), largely composed of young adults aged 20–40 years (61.8%), with unmarried individuals accounting for 63%. Conversely, the RT group consisted mainly of middle-aged and older adults married women (58.2%), with a higher proportion undergoing first-time testing (72.5%). Notably, the HIV positive rate in the PITC group dropped significantly in 2023 and 2024, reaching 0.20 and 0.30% respectively, potentially due to the “dilution effect” following an expansion of the testing population or issues related to data quality.ConclusionPITC demonstrated significant improvements in HIV testing efficiency during 2017–2022.